The information needs of people with degenerative cervical myelopathy: A qualitative study to inform patient education in clinical practice. - Irina Sangeorzan; Panoraia Andriopoulou; Benjamin M Davies; Angus McNair (PLoS ONE, 2023)
Background Individuals with lifelong illnesses need access to adequate information about their condition to make optimal health decisions. Degenerative Cervical Myelopathy (DCM) is the most common form of spinal cord dysfunction in adults worldwide. Its chronic and debilitating nature, varied impact, clinical trajectory, and management options necessitate appropriate informational support to sustain effective clinical and self-directed care strategies. However, before clinicians can meet patients' information needs, they must first have an understanding of their baseline requirements. This study explores the information needs of people with DCM (PwCM). In doing so, it provides a starting point for the development of patient education and knowledge management strategies in clinical practice. Methods Semi-structured interviews with PwCM were conducted using an interview guide. Interviews were audio-recorded and transcribed verbatim. Thematic analysis according to Braun and Clarke's six-phase approach was used to analyse the data. Findings were reported according to the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Results Twenty PwCM (65% female, 35% male), with ages ranging from 39 to 74 years old participated in the interviews. The findings indicated that the provision of information to PwCM during clinical interactions varies. Accordingly, PwCM's information needs were broad-ranging, as was the nature of the information they found useful. Three main themes were identified (1) Variation in the provision of information to PwCM during clinical interactions, (2) Variations in the information needs of PwCM, and (3) Information that PwCM find useful. Conclusion Efforts must turn to adequately educating patients at the time of the clinical encounter. A comprehensive and consistent patient-centered information exchange in DCM is necessary to achieve this.